Scan-to-BIM and segmentation processes for the conservation of cultural heritage. A workflow proposal - Saverio D'Auria; Pierpaolo D'Agostino (Disegnare con)
The ongoing technological development in the AEC sector is also radically influencing the area of cultural heritage, which is notoriously very conservative. The processes of digitisation of the historical architecture and archaeological heritage are giving great pulse to projects and programmes aimed at physical and cultural accessibility, conservation, tourist attractiveness, dissemination and scientific research with positive effects in terms of enhancement and visibility. 3D survey, H-BIM and scan-to-BIM processes, Machine Learning and Artificial Intelligence applications are contributing to a methodological and design approach revolution referred to cultural heritage. This paper shows a workflow related to the analysis of the degradation of ancient surfaces and its digital transposition on parametric models through the semi-automatic segmentation of high-resolution images. The goal is to provide a useful tool for populating ultra-specialized information in BIM environment for maintenance and restoration activities. The case study on which the methodology was applied is a part of the western fortifications of the Aragonese Castle of Ischia; these protect Piazza d’Armi, are overlooking the sea and incessantly subjected to the corrosive actions of the wind, salt and rain. The object has been identified for its intrinsic inaccessibility and the consequent difficulties to intervene with traditional survey and analysis of degradation approaches. The research is part of a scientific collaboration agreement between the Department of Civil, Building and Environmental Engineering of the University of Naples Federico II and the Aragonese Castle s.a.s. which is producing studies and research on architectural emergencies inside the fortified citadel. DOI: https://doi.org/10.20365/disegnarecon.32.2024.13